Operation Christmas Child: a story of simple gifts - Graham, Franklin (B & H Publishing Group, 2013)
"It was a simple idea that became the worldwide outreach of Operation Christmas Child, a project of Samaritan's Purse, to minister to children in war-torn and famine-stricken countries. In just two decades it has inspired everyday people to provide more than 100 million gift-filled shoeboxes to needy children in 130 countries. This beautiful book weaves the moving, God-saturated story of the ministry's beginning with the soul-stirring, Christ exalting stories of lives that have been forever changed by a simple shoebox."--Dustjacket